2022
DOI: 10.1177/11206721221091367
|View full text |Cite
|
Sign up to set email alerts
|

Low-vision rehabilitation in Italy: Cross-sectional data from the Device and Aids Registry (D.A.Re)

Abstract: Objectives We are reporting on the characteristics of low-vision adults attending large rehabilitation services which provide data to D.A.Re (Devices & Aids REgister) in Italy. D.A.Re aims to gather information about low-vision aids owned by Italian patients with visual impairment. Methods We included consecutive patients attending low-vision rehabilitation centres providing data to D.A.Re from 2019 to July 2021. Demographic features, self-reported use of technology and aids, vision performance, and the In… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 9 publications
0
5
0
Order By: Relevance
“…(19) A strength of our study is the multicentre data collection in different low-vision services affiliated with the Italian Union for the Blind and Visually Impaired, using a standardised data collection which has previously been validated. (7) Moreover, since vision impairment is a dynamic condition, a pragmatic approach was adopted linking actual use of a given device at the moment of the clinical encounter to IADL and reading performance.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…(19) A strength of our study is the multicentre data collection in different low-vision services affiliated with the Italian Union for the Blind and Visually Impaired, using a standardised data collection which has previously been validated. (7) Moreover, since vision impairment is a dynamic condition, a pragmatic approach was adopted linking actual use of a given device at the moment of the clinical encounter to IADL and reading performance.…”
Section: Discussionmentioning
confidence: 99%
“…The widespread interest in this topic led us to collect clinical and personal data of patients affected by low vision disability using low-vision devices in a specific national registry. 7 The Device & Aids Register (D.A.Re), was created in 2019 by the National Institute for Device and Technology Assessment (Istituto Nazionale Valutazione Ausili e Tecnologie, INVAT) to collect individual data from several low-vision rehabilitation centres, many of which are part of the Italian Union for the Blind and Visually Impaired (Unione Italiana Ciechi e Ipovedenti, UICI). 7 The aim of this study is to investigate the characteristics of electronic device users, specifically of users of smartphones and tablets, as well as the reported Instrumental Activity of Daily Living (IADL) score and its associations with patients' characteristics in users and non-users of these devices.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…In one study of patients attending low-vision clinics in Italy, those with good self-reported computer knowledge who used optical aids and computer-based software were more likely to have higher quality of life scores than those without. Assistive technology devices, in particular, were found to be highly beneficial [21 ▪ ].…”
Section: Benefits Of Vision Rehabilitation/rationale For Treatmentmentioning
confidence: 99%